2022
DOI: 10.1002/mdc3.13603
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of Dopamine Replacement for Dynamic Facial Expressions in Parkinson's Disease

Abstract: Background Current conflict exists regarding the potential beneficial effects of dopamine medications on facial expressivity in Parkinson's disease. Via digital video analysis software, we previously found reduced facial movement (entropy) and slower time to reach peak entropy in individuals with Parkinson's disease compared to controls. Objectives We aimed to determine whether levodopa medications improved parameters of dynamic facial expressions (amplitude, speed). Methods A total of 34 individuals with idio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Under these conditions, hypomimia scores were significantly lower in ON condition than in OFF. Finally, a recent study testing dynamic facial expression, measured through an entropy video analysis of facial movement, showed greater facial movements in ON compared with OFF condition [58]. All these findings suggest a potential beneficial effect of dopaminergic treatment on hypomimia in PD patients.…”
Section: Pharmacological Treatmentsmentioning
confidence: 74%
See 4 more Smart Citations
“…Under these conditions, hypomimia scores were significantly lower in ON condition than in OFF. Finally, a recent study testing dynamic facial expression, measured through an entropy video analysis of facial movement, showed greater facial movements in ON compared with OFF condition [58]. All these findings suggest a potential beneficial effect of dopaminergic treatment on hypomimia in PD patients.…”
Section: Pharmacological Treatmentsmentioning
confidence: 74%
“…This association has been investigated in other studies reporting correlations between hypomimia severity and bradykinesia, rigidity, and axial symptoms [51][52][53][54], suggesting a prominent role of dopaminergic system derangement in the genesis of hypomimia. Indeed, hypomimia severity has been recently associated with the level of nigrostriatal dopaminergic degeneration [55,56], and some studies reported the improvement of facial movement after L-DOPA administration [51,52,57,58]. Interestingly, hypomimia seems to improve during sleep [59].…”
Section: Blinking and Voluntary Movementsmentioning
confidence: 99%
See 3 more Smart Citations